Economic planning and development in Espírito Santo: a case study (1950-1980) (Ágora Journal, 2026)
This article aims to analyze the planning strategies and the development process implemented in Brazil and in the state of Espírito Santo between the 1950s and the 1980s, as well as their unfolding and impacts on economic, social, and institutional dynamics at both the national and regional levels. Furthermore, it contextualizes the main governmental initiatives aimed at industrialization, productive modernization, and territorial integration, considering the political and economic context that characterized the period. Finally, the methodology adopted is based on a qualitative approach through bibliographic analysis, encompassing academic works and historical studies that allow for a critical and in-depth interpretation of the proposed theme, based on the selected historical framework.
Keywords: Development; Planning; Espírito Santo.